Behavioural and structural analysis of stakeholders in E-waste management. (2022) - Pandey, Jyotsna; Kaushal, Rajendra Kumar; Shukla, Sheo Prasad
Abstract: In this paper an Electronic Waste Management EWM model is developed and strategies of various associates are explored with the help of Non cooperative Game theory to solve the problem of WEEE from the environment. Gambit Software is used as tool to compute the Nash equilibrium and find out the best strategy for various associates in EWM model. The probability and the payoff profile computed represents the strictly dominated or weakly dominated and mixed strategy exhibits the strategies to be followed by all involved stakeholders in EWM model. The purpose of computation of Nash equilibrium to create a feasible model and suitable to sort out the problem of WEEE for all stakeholders in present EWM model. In present study Green Tax is not considered. Five stake holders has been considered i.e. Government Regulatory Bodies, Manufacturing Unit, Recycling Unit, Collector and Consumer. GRBs are opting Penalty strategy and getting payoff of 582.25$, MU is opting EPR + PRO strategy and getting payoff −1885.29$, RU is opting CP strategy and getting payoff 402.26$, COLL is opting CBC strategy and getting payoff 234.49$ and CS is opting EX strategy.